Vestibular performance in high-level soccer and ice hockey players: Sport-specific norm values and implications - Tarnutzer, A. A.; Weber, K. P.; Bockisch, C. J.; Straumann, D.; Feddermann-Demont, N. (Journal of Science and Medicine in Sport, 2022)
Objectives: Quantitative vestibular testing in athletes after sports-related concussion (SRC) has become more popular due to accompanying injuries of the peripheral-vestibular organs that require targeted treatment. Sports-specific normative values are currently not available. Taking into account potential adaptational mechanisms, we obtained sports-specific, age- and peak-head-velocity-corrected normative values of peripheral-vestibular function and postural-stability in football (soccer, FB) and ice-hockey (IH) players. Design: Retrospective single-center case-control study. Method: Pre-seasonal angular vestibulo-ocular reflex (aVOR) gains and cumulative-saccadic-amplitudes were obtained using the video-head-impulse test and performance in the balance-error-scoring-system (BESS) was recorded and compared in high-level FB-players (n = 510, 197 females) and IH-players (n = 210, males only) (age-range = 13-39y) and in healthy normals (n = 49, 22 females). Statistical analysis was performed using a generalized linear model. Results: aVOR-gain values were significantly higher for FB-players than for IH-players (1.07 ± 0.21 vs. 0.98 ± 0.13, p < 0.001) and controls (1.07 ± 0.21 vs. 0.97 ± 0.17, p < 0.001). Significant age-related changes in aVOR-gains were only observed for the anterior and posterior canals in the IH-players. Cumulative-saccadic-amplitudes were clearly below established cut-off values (0.73°/trial). BESS scores were significantly higher in IH-players than in FB-players (15.4 ± 5.1 vs. 11.2 ± 4.9, p < 0.001). Conclusions: The significantly better performance of the FB players in the vertical aVOR-gains and the BESS compared to the IH-players could be related to sports-specific differences influencing visuo-vestibular and balance performance. Therefore, we recommend using the established normative aVOR-gain values for high-level FB-players, whereas in IH obtaining individual pre-seasonal (baseline) aVOR-gain values is proposed. Further studies should add sports-specific normative aVOR-gain values for IH and other sports.